2009
DOI: 10.1108/17473610910940774
|View full text |Cite
|
Sign up to set email alerts
|

Exergaming: virtual inspiration, real perspiration

Abstract: Purpose -The USA is facing an obesity crisis so large that for the first time in history, this generation of children may have a life span that does not exceed that of its parents. Simultaneously, the gaming industry has introduced a form of video gaming (e.g. Nintendo Wii) that requires the participant to be physically involved in the game. For example, a live player will have a tennis racquet that he/she swings to compete with a virtual opponent on screen. This form of entertainment has been termed ''exergam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…Making exercise entertaining and fun may open the door to seeing opportunities to be active in other parts of their day [5]. Other research on exergames has shown that beyond the benefits associated with added activity minutes, these kinds of games may increase a player's fitness motivation [10]. While we did not investigate individual children's exercise self-efficacy, with increased practice we expect children's fine and gross motor skills as well as their fitness levels may also improve.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Making exercise entertaining and fun may open the door to seeing opportunities to be active in other parts of their day [5]. Other research on exergames has shown that beyond the benefits associated with added activity minutes, these kinds of games may increase a player's fitness motivation [10]. While we did not investigate individual children's exercise self-efficacy, with increased practice we expect children's fine and gross motor skills as well as their fitness levels may also improve.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we investigate the effects of an exergame built on an educational platform delivered in the classroom environment, combining body weight exercises with math skill practice, on activity, academic performance and classroom behavior. In contrast to Klein and Simmers [10], classroom use of exergames may provide external motivation by empowering teachers to play a critical role in increasing activity levels of children. If teachers believe that the time spent on exergames can not only increase activity levels but also advance the academic and behavior goals they have for their classrooms, devoting time to activity within the school day may increase.…”
Section: Exergamingmentioning
confidence: 94%
See 2 more Smart Citations
“…VOAGs allow for cooperative and competitive play over the Internet with others players enabling participants to engage in PA that expands the pool of participants from proximal to an online community of participants thereby increasing opportunities for participation. AVGs allow players to enter virtual worlds, helping them into flow while playing [105,106]. Flow Theory relates to a participants persistence to play [105].…”
mentioning
confidence: 99%